2020
DOI: 10.1017/s0021859621000435
|View full text |Cite
|
Sign up to set email alerts
|

Model-based yield gap analysis and constraints of rainfed sorghum production in Southwest Ethiopia

Abstract: For ensuring food demand of the fast growing population in developing countries, quantification of crop yield gaps and exploring production constraints are very crucial. Sorghum is one of the most important climate change resilient crops in the rainfed farming systems of semi-arid tropics. However, there is little information about yield gaps and production constraints. This study aimed at analysing existing yield gaps and exploring major constraints of sorghum production in Southwest Ethiopia. A crop simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
3
7
0
Order By: Relevance
“…Galilea variety was high yielder than Cochoro variety which implies that a higher yielder improved seed can cause a remarkable improvement in tomato production for smallholder farmers. This is in line with [31] that reported that seeds that fulfill the quality requirements have a positive impact on the productivity of land.…”
Section: B Effect Of Socio-economics and Farm Tomato Productionsupporting
confidence: 91%
See 2 more Smart Citations
“…Galilea variety was high yielder than Cochoro variety which implies that a higher yielder improved seed can cause a remarkable improvement in tomato production for smallholder farmers. This is in line with [31] that reported that seeds that fulfill the quality requirements have a positive impact on the productivity of land.…”
Section: B Effect Of Socio-economics and Farm Tomato Productionsupporting
confidence: 91%
“…This implies that policy interventions that make improved Gelilea variety seed available to more farmers could enhance productivity. The result is in line with [29,31,38] who stated that the choices accessible to farmers' new high yielder variety at a reasonable price, and at the right place and time contribute to increased crop productivity.…”
Section: Factors Affecting Tomato Productivity Of Smallholder Farmerssupporting
confidence: 81%
See 1 more Smart Citation
“…The effect of temperature on species could be cultivar‐specific regarding timing, intensity, and duration of stress (Opole et al., 2018; Prasad & Maduraimuthu, 2014). Studies indicate that treatments and environmental interactions can have a substantial effect on yield differences among cultivars (Chala, 2021; Habte et al., 2020). In the current study, the yield reduction projected for cultivar EH‐1493 (−19.7%) was lower than the reduction projected for cultivar Traveller (−44.4%) averaged across all study areas, models, and RCPs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding well agreed with Kanda et al (2021) where they reported that AquaCrop model over-estimated cowpea yield under water deficit conditions. High over-estimations of sorghum yield especially during water deficit conditions have been reported by Habte et al (2020) using AquaCrop and DSSAT models. The SIMPLACE insignificantly simulation of yield during water deficit could be attributed to the possible errors in the determination of canopy senescence (Espadafor et al, 2017).…”
Section: Articlementioning
confidence: 99%